Six new species of Coproptilia Snellen, 1903 (Lepidoptera: Lecithoceridae: Lecithocerinae) from Vietnam - Park, Kyu-Tek; Heppner, John B.; Yu, Tae-Uk (Zootaxa, 2026)
Six new species of Coproptilia Snellen, 1903 are described from Vietnam. The new species are: Coproptilia septentrionalis, sp. nov., C. cheongae, sp. nov., C. calcaneoides, sp. nov., C. gounella, sp. nov., C. baviana, sp. nov., and C. campestris, sp. nov. Adults and their genitalia of the new species are illustrated. In addition, three species of the genus Coproptilia: C. acriella (Park, 2002), C. abunda (Yu & Wang, 2019), and C. fusoidea (Yu & Wang, 2019), are reported for the first time from Vietnam. At the same time, C. fusoidea (Yu & Wang, 2019) is also reported for the first time from Thailand. Subsequently, a total of 32 species belonging to the genus Coproptilia Snellen are enumerated.